2016
DOI: 10.1038/onc.2016.458
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-FOXP3 directly activated CCL5 to recruit FOXP3+Treg cells in pancreatic ductal adenocarcinoma

Abstract: Forkheadbox protein 3 (FOXP3), initially identified as a key transcription factor for regulatory T cells (Treg cells), was also expressed in many tumors including pancreatic ductal adenocarcinoma (PDAC). However, its role in PDAC progression remains elusive. In this study, we utilized 120 PDAC tissues after radical resection to detect cancer-FOXP3 and Treg cells by immunohistochemistry and evaluated clinical and pathological features of these patients. Cancer-FOXP3 was positively correlated with Treg cells acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(158 citation statements)
references
References 49 publications
7
151
0
Order By: Relevance
“…23 However, the functions of Foxp3 on different cancer are controversial. [24][25][26] Our previous research found that ectopic tumoral Foxp3 can promote gastric cancer proliferation, migration and invasion. 27 Therefore, it is necessary to verify whether Foxp3 is involved in miR-664a-3p/MOB1A axis.…”
Section: Introductionmentioning
confidence: 99%
“…23 However, the functions of Foxp3 on different cancer are controversial. [24][25][26] Our previous research found that ectopic tumoral Foxp3 can promote gastric cancer proliferation, migration and invasion. 27 Therefore, it is necessary to verify whether Foxp3 is involved in miR-664a-3p/MOB1A axis.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is additionally supported by the fact that in the whole NPC group there was worse survival if macrophage markers and FOXP3 were low. Blockade of Tregs as a therapeutic option in NPC50 should therefore be cautiously studied as FOXP3 has also been shown to be a tumour suppressor 51…”
Section: Discussionmentioning
confidence: 99%
“…PDAC cells recruit immunosuppressive tumourassociated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs) from the peripheral circulation via the CCL2/CCR2 axis [14]. PDAC cells express high levels of CCL5 to recruit regulatory T cells (Treg cells) through CCR5 [15], and this process may partially explain the recruitment of Treg cells to PDAC lesions [16]. Approximately 12.5% of PDAC patients are reported to positively express programmed cell death protein ligand-1 (PD-L1) [17], which induces T cell anergy and apoptosis through programmed cell death protein-1 (PD-1) expressed on T Fig.…”
Section: Pdac Epithelial Cellsmentioning
confidence: 99%